2021
DOI: 10.1021/acsomega.1c02952
|View full text |Cite
|
Sign up to set email alerts
|

Pore Structure and Movable Fluid Characteristics of Typical Sedimentary Lithofacies in a Tight Conglomerate Reservoir, Mahu Depression, Northwest China

Abstract: The pore structure and movable fluid characteristics of tight conglomerate reservoirs are complex, which are greatly different from conventional reservoirs. The depositional mechanism is the fundamental factor controlling the physical properties of conglomerate reservoirs. However, there is a lack of systematic research on the pore structure and movable fluid characteristics of conglomerate reservoirs with typical sedimentary facies. This paper investigates the pore structure and movable fluid characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…The movable fluid porosity of a sample is influenced by multiple factors such as mineral composition and rock grain size. Previous studies have shown a weak positive correlation between movable fluid porosity and rock brittle mineral content and grain size. Sample NS1 had a large grain size and developed large dissolution pores contributing to the movable fluid porosity (Table and Figure ). In contrast, the movable fluid of samples NS2 and NS3 was mainly distributed in nanopores and submicrometer pores leading to an unclear relationship with mineral content and grain size.…”
Section: Resultsmentioning
confidence: 85%
“…The movable fluid porosity of a sample is influenced by multiple factors such as mineral composition and rock grain size. Previous studies have shown a weak positive correlation between movable fluid porosity and rock brittle mineral content and grain size. Sample NS1 had a large grain size and developed large dissolution pores contributing to the movable fluid porosity (Table and Figure ). In contrast, the movable fluid of samples NS2 and NS3 was mainly distributed in nanopores and submicrometer pores leading to an unclear relationship with mineral content and grain size.…”
Section: Resultsmentioning
confidence: 85%
“…The porosity surpasses the values obtained under the resolution of 13 µm/voxel; however, pores under 2.3 µm remain unidentified at the current resolution. Based on other scholars' research on pore types and characteristics in this area [21], as well as the analysis at micron scale CT images, it reveals that the conglomerate in the study area predominantly comprises three types of pores: (1) secondary dissolution pores, characterized by highly irregular edges in grayscale images, exhibiting isolated spots and pits. These solution holes are believed to result primarily from the dissolution of unstable minerals, such as feldspar cleavage cracks or debris, during early diagenesis.…”
Section: Pore Structure Characteristicsmentioning
confidence: 86%
“…The tight conglomerate is composed of large-sized gravel sediments and the interstitial material, and the pores inside the interstitial material are the main flow channel. The grain size in the interstitial material also varies greatly [21,22]. Therefore, the representative volume size of the tight conglomerate in pore modeling usually needs to be larger than that of tight sandstone or shale, and the range of corresponding pore sizes is also relatively wider.…”
Section: Introductionmentioning
confidence: 99%
“…The marl comprehensive pore distribution can be reflected by the NMR T 2 spectrum (Wu et al, 2021;Zhao et al, 2022). The T 2 spectrum of laminated marl revealed clear bimodal characteristics (Figure 9A), and the right peak was more noticeable, indicating that laminated marl developed not only nanometer micropores but also a certain amount of micrometer macropores.…”
Section: Pore-throat Size Distributionmentioning
confidence: 99%